Hyperthyroid Phase of Hashimoto's Thyroiditis - Siti Nurul Hapsari; Sidarti Soehita (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
Hashimoto thyroiditis (chronic autoimmune thyroiditis) is the most common cause of hypothyroidism in iodine-sufficient areas of the world. This condition, however, can sometimes show hyperthyroidism. A 39-year-old femalewas admitted to hospital due to shortness of breath and tremor four hours before hospitalization. There were nausea, chestpain, cold chills, and palpitation. She was diagnosed with Hashimoto's thyroiditis and routinely received tyrosol,propranolol, and dexamethasone. Physical examination showed cervical mass, afebrile, blood pressure of 130/70 mmHg,pulse rate of 110 beats/minute and respiratory rate of 20 breaths/minute. Laboratory examinations showed WBC 7.53 x 109/L, Hb 11.0 g/dL and platelet count of 168 x 109/L. Chest X-Ray: negative for infiltrates. Several laboratory testswere performed, abnormal results were as follows: FT4 level of 2.96 ng/dL (increased), TSH level of 0.003 µIU/mL(decreased), anti-TPO (antithyroid microsomal antibody) level of 306 IU/ml (increased), and IgE level of 213.6 IU/mL(increased). Peripheral blood smear, coagulation test, serum electrolytes, liver function tests, renal function tests, urinalysis,CEA and Ca 125 were within normal limits. Thyroid ultrasound was performed and showed a benign lesion. Fine needleaspiration biopsy showed lymphocytic Hashimoto's thyroiditis. Echocardiography showed hyperthyroid heart disease. Dueto an increase of anti-TPO and FT4 levels, a decrease of TSH levels and lymphocytic thyroiditis from FNAB, this patient wasdiagnosed with a hyperthyroid phase of Hashimoto's thyroiditis. Thyroid function tests and thyroid antibody tests must bemonitored to distinguish between the hyperthyroid and hypothyroid phase of Hashimoto thyroiditis.